In vitro anti‑inflammatory activity of Elephantopus scaber leaf tea through human red blood cell membrane stabilization - Wahdaniah Wahdaniah; Gervacia Jenny Ratnawaty; Linda Triana; Bagus Muhammad Ihsan (Poltekkes Kemenkes Bandung, 2026)
Background: Inflammation is a physiological response to tissue injury, infection, or irritation. The long-term use of non-steroidal anti-inflammatory drugs (NSAIDs) may cause adverse effects, prompting the search for safer natural alternatives. Tapak liman (Elephantopus scaber L.) leaves contain flavonoids, saponins, tannins, and steroids with potential anti-inflammatory properties. Objective: To evaluate the in vitro anti-inflammatory activity of E. scaber leaf tea using the red blood cell (RBC) membrane stabilization method. Methods: A laboratory experimental study with a post-test-only control group design was conducted. Anti-inflammatory activity was assessed based on the inhibition of hypotonic solution-induced erythrocyte hemolysis. Tapak liman leaf tea was prepared by steeping dried leaf powder in hot distilled water. RBC suspensions at concentrations of 0.25%, 0.5%, and 1% were used. Sodium diclofenac (0.1%) served as the positive control and distilled water as the negative control. Hemolysis was measured spectrophotometrically at 560 nm. Results: Tapak liman leaf tea inhibited erythrocyte hemolysis in a concentration-dependent manner. The highest membrane stabilization activity approached that of sodium diclofenac. All tested concentrations showed significantly greater membrane stabilization than the negative control (p<0.05). Conclusion: Elephantopus scaber leaf tea prepared as a hot-water infusion exhibits significant in vitro anti-inflammatory activity through erythrocyte membrane stabilization and has potential for further development as a natural phytotherapeutic agent.